A study on relationship between job stress and job satisfaction among employee in Sime Darby Plantations Sdn. Bhd. / Muhammad Faiz Mohd Zabidi - Mohd Zabidi, Muhammad Faiz (Faculty of Business and Management, 2011)
This research investigates the relationship between job stress and job satisfaction. The determinants of job stress that have been examined under this study include relationship with others, workload pressure, and performance pressure. The sample consists of an employee in the company Sime Darby Plantation Sdn. Bhd. Malaysia. Job life is one of the important parts in our daily lives which cause a great deal of stress. Due to the competitive nature of the job environment most of the people in the world are spending their time for job related work purposes resulting ignore the stressor those are influencing their work and life. Usually people are more worry about their outcome of their work that can even affect the way they treat other people and how they communicate with their peers and customers. They may feel frustrated when they had problems with their peers and customers. This may leave a negative impact to the organization itself. Therefore, it is very important for employer and employees to realize the stress and the stressor that cause all the negative impact. The number of an employee in company Sime Darby Plantation Sdn. Bhd. Had increased tremendously for the past few years due to the mergers and acquisition action by the company itself with two giant plantations company in Malaysia, Guthrie Berhad and Golden Hope Plantation Bhd. Sime Darby Plantation Sdn. Bhd. A merger happens when two companies combined together into one entity (Sherman, 2005). Generally, in a merger, the involved companies‟ shareholders will be remains as joint owners. Nevertheless, the involved companies will combine their resources in order to achieve common goals. The involved companies will become into a new legal entity (Buckley & Ghauri, 2002). Staffs may face more problems in their job as the company become bigger than before and the workload may also increase due to the action taken by the company to merge with the two giant companies. The merge company are now setting their own new goal to that their staff are involving with the ultimate goal. This may causes the employee itself to face plenty of stress and therefore affect their satisfaction and even their physical or mental health. The aim of this study is to identify the stressors issues that will influence the employee job satisfaction.